1993
DOI: 10.1161/01.str.24.12.2087
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic variation of the middle cerebral artery in the Sprague-Dawley rat.

Abstract: Results: Six distinct branching patterns were observed. The majority (82.9%) of middle cerebral arteries studied conformed to the typical bifurcating vessel commonly referred to in the literature. However, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 22 publications
(7 reference statements)
3
40
0
1
Order By: Relevance
“…However, there was considerable variation in the rate and extent of expansion. The reason for the variability was not determined in this study, but may be related to variations in cerebral vasculature (33) and intralumenal-suture placement. The observation that the CBF threshold associated with the ADC 15 area either does not change or changes only slightly, and the results presented in Table 2 suggest that the spread of the ADC 15 area may be attributable, at least in part, to an increase in the area with CBF levels below the threshold for energy failure.…”
Section: Discussionmentioning
confidence: 81%
“…However, there was considerable variation in the rate and extent of expansion. The reason for the variability was not determined in this study, but may be related to variations in cerebral vasculature (33) and intralumenal-suture placement. The observation that the CBF threshold associated with the ADC 15 area either does not change or changes only slightly, and the results presented in Table 2 suggest that the spread of the ADC 15 area may be attributable, at least in part, to an increase in the area with CBF levels below the threshold for energy failure.…”
Section: Discussionmentioning
confidence: 81%
“…The authors used cortical blood flow and apparent diffusion co-efficient maps and 2,3,5-Triphenyltetrazolium chloride staining to arrive at that conclusion (Bardutzky et al, 2005). Other studies have also confirmed differences in the middle cerebral artery occlusion model in different strains (Fox et al, 1993;Sauter et al, 1995;Oliff et al, 1996). The rat model for middle cerebral artey was first described by Robinson et al in 1975 and has since been modified by several groups (Tamura et al, 1981;Bederson et al, 1986).…”
Section: Are Hsc a Viable Avenue For Stroke Therapy?mentioning
confidence: 95%
“…However, although one of the major advances of stroke research has been through the development of reproducible techniques for the induction of focal or global ischemia in animals, the fact remains that there is a substantial number of variants of those in vivo bioassays. 7 Thus, the development of experimental strategies that improves the specificity of the assay and saves animal is a challenge. A probable solution to these problems can be an in vitro neuronal cell culture system, which allows the monitoring of pharmacological effects in an animal-saving and organspecific manner.…”
Section: Introductionmentioning
confidence: 99%